An Estimation Method for Potential Storm Surge Heights Using a New Typhoon Initialization Technique - MURAKAMI, Tomokazu; YASUDA, Takashi; KOBAYASHI, Kosuke; YOSHINO, Jun (PROCEEDINGS OF COASTAL ENGINEERING, JSCE, 2007)
A new application of modifying initial three-dimensional typhoon meteorologica flields for a mesoscale atmospheric model is developed in this study to evaluate potential storm surge heights that are likely to occur under expected global warming. The initialization technique based on the potential vorticity invertibility principal can arbitrarily control the position and intensity of typhoon in the initial atmospheric conditions, consistent with the balance wind and hydrostatic equilibrium. Preliminary numerical experiments of storm surge scenarios in Ise Bay, using a coupled atmosphere-ocean-wave model, show that the subtle difference of typhoon track causes a large impact on the spatial distribution of storm surge level.